Lateral and Medial Ventral Occipitotemporal Regions Interact During the Recognition of Images Revealed from Noise - Nordhjem, Barbara; Ćurčić-Blake, Branislava; Meppelink, Anne Marthe; Renken, Remco J.; de Jong, Bauke M.; Leenders, Klaus L.; van Laar, Teus; Cornelissen, Frans W. (Frontiers in Human Neuroscience, 2016)
Several studies suggest different functional roles for the medial and the lateral ventral sections in object recognition. Texture and surface information is processed in medial regions, while shape information is processed in lateral sections. This begs the question whether and how these functionally specialized sections interact with each other and with early visual cortex to facilitate object recognition. In the current research, we set out to answer this question. In an fMRI study, thirteen subjects viewed and recognized images of objects and animals that were gradually revealed from noise while their brains were being scanned. We applied dynamic causal modeling (DCM) – a method to characterize network interactions – to determine the modulatory effect of object recognition on a network comprising the primary visual cortex (V1), the lingual gyrus (LG) in medial ventral cortex and the lateral occipital cortex (LO). We found that object recognition modulated the bilateral connectivity between LG and LO. Moreover, the feed-forward connectivity from V1 to LG and LO was modulated, while there was no evidence for feedback from these regions to V1 during object recognition. In particular, the interaction between medial and lateral areas supports a framework in which visual recognition of objects is achieved by networked regions that integrate information on image statistics, scene content and shape – rather than by a single categorically specialized region – within the ventral visual cortex.